2000
DOI: 10.1016/s1010-7940(00)00427-9
|View full text |Cite
|
Sign up to set email alerts
|

Results with the Novacor assist system and evaluation of long-term assistance✩

Abstract: LVAD Novacor has provided reliable mechanical performance and good hemodynamic improvement. Most complications seem to occur in the first 90 days, therefore long-term assistance could be considered. A reduction of the high rate of thromboembolic complications remains mandatory to improve the clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…With the use of these devices, the rate of survival from the time of implantation to the time of transplantation has ranged from 51 to 71 percent. [5][6][7][8][9] Worldwide, more than 5000 patients have received these devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the use of these devices, the rate of survival from the time of implantation to the time of transplantation has ranged from 51 to 71 percent. [5][6][7][8][9] Worldwide, more than 5000 patients have received these devices.…”
Section: Resultsmentioning
confidence: 99%
“…Among the patients who received the device on a per-protocol basis, the rate of survival to transplantation was 79 percent. Previous studies of approved devices [5][6][7][8][9] have reported rates of survival to transplantation of 51 to 71 percent with left ventricular assist devices and 58 to 61 percent with biventricular assist devices.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with these very early devices, it was clear they could improve hemodynamics, reverse end-organ damage and reduce symptoms, [5] however; this came at a price of long hospital stays. By 1998, electric powered devices which were intra-corporeal and freed patients from tethering to a console were being used as a bridge to transplantation, most notably the Heartmate VE (Thermocardiosystems) [6] and Novacor (Baxter) [7]. The ability to discharge a patient home was a critical step forward which led to the field taking a great leap - testing devices in end stage patients who were not transplant candidates [8].…”
Section: Historical Perspectivementioning
confidence: 99%
“…In 2002, the FDA believed that it might be more appropriate to rely on a performance goal using prospectively identified criteria to define success for bridging patients to cardiac transplantation in order to facilitate single-arm clinical trials. After an extensive literature review, six publications were used as the basis for this performance goal [2][3][4][5][6][7]. These papers supported a 65-70% survival to cardiac transplantation rate as the performance goal for approved BTT devices.…”
Section: Development and Use Of The Btt Performance Goalmentioning
confidence: 99%